Analysis of the association between lactotransferrin (LTF) gene polymorphism and dental caries - Azevedo, Luiza Foltran; Pecharki, Giovana Daniela; Brancher, João Armando; Cordeiro Junior, Carlos Alberto; Medeiros, Kamilla Gabriella dos Santos; Antunes, Alessandra Armstrong; Arruda, Eduardo Silva; Werneck, Renata Iani; Azevedo, Luciana Reis de; Mazur, Rui Fernando; Moysés, Samuel Jorge; Moysés, Simone Tetü; et al. (Journal of applied oral science, 2010)
The present study evaluated the association between lactotransferrin (LTF) gene polymorphism (exon 2, A/G, Lys/Arg) and dental caries. A convenience sample of 110 individuals, 12 years old, was divided into: group 1, 48 individuals without caries experience (DMFT=0), and group 2, 62 subjects with caries experience (DMFT>or=1). DNA was obtained from a mouthwash with 3% glucose solution, followed by a scrapping of the oral mucosa. After DNA purification, polymerase chain reaction (PCR), single strand conformation polymorphism (SSCP) was performed to access the study polymorphism. The LTF A/G (Lys/Arg) polymorphism had been previously reported as located in exon 1. Allele 1 of the study polymorphism was associated with low DMFT index and showed a protective effect against caries experience (OR=0.16, IC=0.03-0.76, p=0.01). Lactotransferrin A/G (exon 2, Lys/Arg) polymorphism was associated with susceptibility to dental caries in 12-year-old students.